2024
DOI: 10.7759/cureus.52482
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the Ponseti Method in the Management of Clubfoot: A Systematic Review

Hassan B Maghfuri,
Ali A Alshareef

Abstract: Clubfoot is a congenital abnormality of the lower extremities, and it may be unilateral or bilateral. Left untreated, it may lead to issues with walking. Additionally, inappropriate treatment or the lack of treatment can result in functional damage. The goal of clubfoot treatment is to correct the deformities of the involved components. The Ponseti method has been regarded as the gold standard for the treatment of clubfoot as it is safe and effective. In this review, we aimed to assess the success of the Ponse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have observed that CTEV was associated with deletion of CASP10 , an apoptosis regulatory gene on chromosome 2 (2q31-33)[ 7 ]. Other suggested causes include abnormalities of joint and/or bone formation, uterine restriction (oligohydramnios), and neurological and vascular abnormalities that occur in the second trimester of pregnancy[ 1 , 8 ]. Numerous studies have reported male sex, maternal age, maternal smoking, maternal marital status, maternal education, and maternal diabetes as associated with increased risk of CTEV[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed that CTEV was associated with deletion of CASP10 , an apoptosis regulatory gene on chromosome 2 (2q31-33)[ 7 ]. Other suggested causes include abnormalities of joint and/or bone formation, uterine restriction (oligohydramnios), and neurological and vascular abnormalities that occur in the second trimester of pregnancy[ 1 , 8 ]. Numerous studies have reported male sex, maternal age, maternal smoking, maternal marital status, maternal education, and maternal diabetes as associated with increased risk of CTEV[ 9 ].…”
Section: Introductionmentioning
confidence: 99%